Information System Security Audit Based on the DSS05 Framework Cobit 5 at Higher Education XX - Sinaga, Rudolf; Samsinar, Samsinar; Afriany, Renny (Universitas Jember, 2021)
Currently, information has become a commodity or basic need, it can even be said that we are already in an